Evaluation of An Existing System Using The System Usability Scale (SUS) as A Guideline for System Improvement - Anam, M. Khairul; Susanti, Susanti; Nurjayadi, Nurjayadi; Zoromi, Fransiskus; Sari, Atalya Kurnia (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2025)
The e-Polvot system at the University of Science and Technology Indonesia (USTI) is a digital platform used for student elections, replacing traditional paper-based voting to enhance efficiency and minimize election fraud. This study evaluates the system using the System Usability Scale (SUS) to assess its usability, including efficiency, effectiveness, and user satisfaction. However, SUS alone does not determine failure points but provides a usability score that reflects user perception. A survey was conducted with 88 respondents from three different academic programs, which showed that while the system generally received a